Conductive Metal‐Organic Frameworks Bearing M−O4 Active Sites as Highly Active Biomass Valorization Electrocatalysts. Issue 13 (16th September 2021) - Zhang, Yuxuan; Kornienko, Nikolay
Abstract: The electrochemical oxidation of the biomass platform 5‐hydroxymethylfurfural (HMF) to 2, 5‐furandicarboxylic acid (FDCA), is an important reaction in the emerging area of renewable energy‐powered biomass valorization. A key limitation in this field is the ill‐defined nature of the catalytic sites of the highest‐performing materials that limits the fundamental insights that can be extracted. To this end, a conductive metal‐organic framework‐based electrocatalytic model system with well‐defined M−O4 active sites for electrochemical HMF oxidation was developed. These materials were found to be highly active towards FDCA generation, with product yields of over 95 %. In parallel, infrared spectroscopy was employed to capture a surface‐bound aldehyde group as the key intermediate in the catalytic cycle, which forms once M(II/III) oxidation occurs. This work illustrates the advantage of utilizing molecularly defined active sites coupled with operando spectroscopy to provide fundamental insights into a variety of electrosynthetic reactions and thus paves the way for future catalyst design. Abstract : Conductive framework electrocatalysts : Conductive metal‐organic frameworks are studied with a combination of electrochemical and spectroscopic techniques. The results indicate that their unsaturated transition metal sites are highly active for the oxidation of biomass platforms (5‐hydroxymethylfurfural) into value‐added chemical products.